2024
DOI: 10.3389/fnagi.2023.1278322
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing default electronic health record tools to improve safety for hospitalized patients with Parkinson’s disease

Allan D. Wu,
Benjamin L. Walter,
Anne Brooks
et al.

Abstract: Electronic Health Record (EHR) systems are often configured to address challenges and improve patient safety for persons with Parkinson’s disease (PWP). For example, EHR systems can help identify Parkinson’s disease (PD) patients across the hospital by flagging a patient’s diagnosis in their chart, preventing errors in medication and dosing through the use of clinical decision support, and supplementing staff education through care plans that provide step-by-step road maps for disease-based care of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We reported that our research highlights the potential of microcurrent therapy as an alternative, non-pharmacological treatment for mitigating cognitive decline and neuroinflammation in Alzheimer’s disease. Microcurrent (MC) stimulation therapy is a therapeutic approach that employs a current of less than 1000 μA, measured in milliampere-hours (mA), which is barely perceptible to the human body [ 19 ]. A study of the literature reveals that the mechanism of MC therapy may involve the modulation of neuroinflammation, particularly through the regulation of MAPK signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that our research highlights the potential of microcurrent therapy as an alternative, non-pharmacological treatment for mitigating cognitive decline and neuroinflammation in Alzheimer’s disease. Microcurrent (MC) stimulation therapy is a therapeutic approach that employs a current of less than 1000 μA, measured in milliampere-hours (mA), which is barely perceptible to the human body [ 19 ]. A study of the literature reveals that the mechanism of MC therapy may involve the modulation of neuroinflammation, particularly through the regulation of MAPK signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…This modulation is hypothesized to reduce neuroinflammatory proteins, thereby potentially improving cognitive function in Alzheimer’s disease [ 20 ]. This therapy holds promising nonpharmacological therapeutic modalities in the treatment of AD, shedding light on the value of developing unconventional therapeutic modalities [ 19 , 20 ]. Thus, our investigation determined that the clinical point balance between enhancing therapeutic effects and mitigating potential neuronal damage is crucial.…”
Section: Introductionmentioning
confidence: 99%